Extensive in situ radiation of feather lice on tinamous. Issue 1921 (26th February 2020) - Virrueta Herrera, Stephany; Sweet, Andrew D.; Allen, Julie M.; Walden, Kimberly K. O.; Weckstein, Jason D.; Johnson, Kevin P.
Abstract : Tinamous host the highest generic diversity of lice of any group of birds, as well as hosting representatives of all four avian feather louse ecomorphs. Although the generic diversity of tinamou feather lice is well documented, few attempts have been made to reconstruct the phylogenetic relationships among these lice. To test whether tinamou feather lice form a monophyletic group as a whole, we used whole-genome sequencing to estimate a higher-level phylogeny of tinamou feather lice, together with a broad diversity of other avian feather louse groups. In total, we analysed sequences from over 1000 genes for 48 genera of avian lice using both concatenated and coalescent approaches to estimate the phylogeny of this diverse group of avian feather lice. Although the body louse ecomorph of tinamou feather lice formed a monophyletic group, they did not strictly form a monophyletic group together with the other three ecomorphs of tinamou feather lice. In particular, a clade comprised of several feather louse genera, mainly from South America, is nested phylogenetically within tinamou lice, which also have their main centre of diversity in South America. These results suggest in situ radiation of these parasites in South America.